Barriers to Safe Motherhood: A Review of Antenatal and Postnatal Care Utilization in Rural India - Rani, Alka; Trivedi, Ankita; Dwivedi, Satyam (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Safe motherhood remains a fundamental public health goal, yet maternal health outcomes in rural India continue to be shaped by deep-rooted social, economic, and structural inequalities. Although India has implemented major maternal health interventions and made significant progress over the past two decades, large gaps persist in the utilization of antenatal care (ANC) and postnatal care (PNC)—services essential for preventing maternal morbidity and mortality. This review synthesizes peer-reviewed sociological, demographic, and public health literature and integrates evidence from NFHS-5 to examine the barriers that rural Indian women face in accessing ANC and PNC. Using a social determinants and gendered power-relations perspective, the paper explores how patriarchal norms, limitations on women’s autonomy, low awareness, cultural meanings of pregnancy, caste and class inequities, economic hardships, geographic isolation, and health system weaknesses jointly undermine maternal healthcare utilization. By weaving together evidence from national surveys and studies by scholars such as Navaneetham and Dharmalingam (2002), Pallikadavath et al. (2004), Kesterton et al. (2010), Hamal et al. (2020), Goli and Niveditha (2014), Girotra et al. (2023), and Thakkar et al. (2023), this review offers an in-depth sociological understanding of why gaps persist. It argues that safe motherhood requires more than biomedical availability; it demands addressing entrenched social structures, redistributing power within households, investing in respectful maternity care, and implementing equity-driven policies that prioritize marginalized communities. The paper concludes with recommendations for gender-transformative community engagement, improved health system responsiveness, financial protection, and culturally informed outreach strategies needed to advance maternal health justice in rural India.